2002
DOI: 10.1046/j.1523-5378.2002.00113.x
|View full text |Cite
|
Sign up to set email alerts
|

A Group‐Specific PCR Assay for the Detection of Helicobacteraceae in Human Gut

Abstract: The novel PCR assay described here is an important new tool in rapid and sensitive assessment for the presence of Helicobacteraceae in human gut.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
36
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 35 publications
(47 reference statements)
2
36
0
Order By: Relevance
“…Basically, two types of PCR assays were developed: speciesspecific PCR assays that allow the identification of single Helicobacter species (27,30) and Helicobacter group-specific PCR assays which can detect several Helicobacter species in a single assay (2,25,27). In samples that are positive in a group-specific PCR a further step is required to identify the Helicobacter species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Basically, two types of PCR assays were developed: speciesspecific PCR assays that allow the identification of single Helicobacter species (27,30) and Helicobacter group-specific PCR assays which can detect several Helicobacter species in a single assay (2,25,27). In samples that are positive in a group-specific PCR a further step is required to identify the Helicobacter species.…”
mentioning
confidence: 99%
“…In samples that are positive in a group-specific PCR a further step is required to identify the Helicobacter species. DNA sequencing and restriction fragment length polymorphism (RFLP) analysis are commonly used for this purpose (2,27), although denaturing gradient gel electrophoresis has also been successfully used (25). Here, we used genusspecific PCR and consecutive DNA sequencing combined with RFLP analysis to evaluate the prevalence of Helicobacter infections and their spread in the SPF facility of our central animal laboratory.…”
mentioning
confidence: 99%
“…A number of research groups have associated this organism with vibrionic hepatitis and enteritis in poultry and with gastroenteritis, diarrhea, and liver and gall bladder disease in human patients (8,9,18,28). It has been suggested that H. pullorum also may play a role in Crohn's disease (1,4).…”
mentioning
confidence: 99%
“…Biopsy specimens from the terminal ileum and the colon of each patient were analyzed by a group-specific PCR assay with primers C97 (5Ј-GCTATGACGGGTATCC-3Ј) and H2 (5Ј-TCGCAATGAGTATTCCTCTT-3Ј) as previously described (2,3). In order to identify the Helicobacter species, amplification products were sequenced as described before (3).…”
mentioning
confidence: 99%